2021
DOI: 10.48550/arxiv.2106.01144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards Emotional Support Dialog Systems

Abstract: Emotional support is a crucial ability for many conversation scenarios, including social interactions, mental health support, and customer service chats. Following reasonable procedures and using various support skills can help to effectively provide support. However, due to the lack of a well-designed task and corpora of effective emotional support conversations, research on building emotional support into dialog systems remains untouched. In this paper, we define the Emotional Support Conversation (ESC) task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…In the future, our work can inspire other approaches to leverage commonsense knowledge for empathetic response generation and similarly promising tasks (e.g. providing emotional support (Liu et al 2021)).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the future, our work can inspire other approaches to leverage commonsense knowledge for empathetic response generation and similarly promising tasks (e.g. providing emotional support (Liu et al 2021)).…”
Section: Discussionmentioning
confidence: 97%
“…Empathy is a desirable trait of human daily conversations that enables individuals to understand, perceive, and respond appropriately to the situation and feelings of others (Keskin 2014). Previous research has demonstrated that empathetic dialogue systems can improve user experience and satisfaction in multiple domains (Fitzpatrick, Darcy, and Vierhile 2017;Liu et al 2021;Wang et al 2021). Hence, it is important to discover ways that allow us to equip open-domain dialogue systems with empathy.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, they are more prone to provide adequate emotional support to users, such as moderate comforting and reasonable suggestions [1479].…”
Section: Empathy and Emotional Supportmentioning
confidence: 99%
“…Emotional Support Dialog Systems. Beyond the trait of being empathetic, advanced dialog systems should also be able to provide effective emotional support for users that are facing ongoing emotional problems [1479]. Emotional support aims at reducing individuals' emotional distress and helping them understand and work through the challenges that they face [1488,1489,1490].…”
Section: Empathy and Emotional Supportmentioning
confidence: 99%
See 1 more Smart Citation